Gamification vs. Teaching First Aid: What Is Being Produced by Science in The Area? - Vancini, Rodrigo; Russomano, Thais; Andrade, Marilia S.; de Lira, Claudio A. B.; Knechtle, Beat; Herbert, Juliana S. (Health Nexus, 2023)
Gamification i.e., the incorporation of game design elements into non-game contexts, represents a transformative tool in health education. In this sense, the increasingly intertwined fields of technology, education, and health present opportunities for informed decision-making and the training of educators, health professionals, and policymakers. This need to improve teaching and learning methods is particularly evident in the areas of first aid and basic life support (BLS), with the aim of improving clinical results and health outcomes. Our article carried out a narrative review, focusing on the intersection of gamification, technology and first aid/BLS training with the aim of investigating the application of gamification and serious games in emergency medicine with the aim of improving motivation and theoretical and practical skills. of health professionals. In addition, this review emphasizes the role of simulation-based education in first aid skills training, highlighting its contribution to preparing first aiders for real-world scenarios. Ultimately, this review underscores the transformative potential of serious games in medical education, showcasing their effectiveness across diverse contexts. In summary, it enhances comprehension of gamification’s role in healthcare and medical education, particularly in first aid training, by underscoring the adaptability and efficacy of serious games in revolutionizing medical and emergency education and healthcare. Nevertheless, it underscores that this remains a relatively underexplored area of knowledge.